Intergenerational Transmission of Educational Attainment in Germany: The Last Five Decades - Guido Heineck; Regina T. Riphahn (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
Over the last decades the German education system underwent numerous reforms in order to improve "equality of opportunity", i.e. to guarantee all pupils equal access to higher education. At the same time internationally comparative evidence yields that Germany features particularly low intergenerational mobility with respect to educational attainment. This study investigates the development in intergenerational education mobility in Germany for the birth cohorts 1929 through 1978 and tests whether the impact of parental background on child educational outcomes changed over time. In spite of massive public policy interventions and education reforms our results yield no significant reduction in the role of parental background for child outcomes over the last decades.
Keywords: I21; I28; J11; 330; education transmission; intergenerational mobility; schooling; human capital transmission; Lohnungleichheit; Einkommensgleichung; Quantilsregression